The Effectiveness of Education through Web-Based Seminar in Increasing Knowledge about the Early Detection and Reporting of Occupational Diseases - Monintja, Keyne Christa; Soemarko, Dewi Sumaryani; Fitriani, Dewi Yunia; Herqutanto, Herqutanto; Wibowo, Suryo (UI Scholars Hub, 2024)
Background: In 2022, the Indonesian Occupational Medicine Association (IOMA) collaborated with oil and gas companies and conducted a web-based seminar (webinar) to enable participants to recognize occupational disease earlier and enhance reporting in companies. We aimed to investigate the effectiveness of the webinar in increasing the intended knowledge. Method: The webinar was separated into three batches, with different participants per batch. Using a one-group pretest-posttest design, we utilized secondary data from IOMA. The effectiveness of the webinar was determined by participants' satisfaction and knowledge as measured by pre-test and post-test. After performing item analysis, we removed poor discriminating items in pre-test and post-test ( Results: Data was gathered from 147 subjects (23.8%, 34%, and 42.2% of the three batches, respectively). Except for company status in the second batch (P = 0.045), there was no significant difference in initial knowledge based on the individual factors studied. Significant knowledge improvement was observed post-webinar in each batch compared to the initial. (P < 0.05). The correlation between satisfaction and post-test scores was negligible (r < 0.3; P > 0.05). Conclusion: The initial knowledge of oil and gas company workers in early detection and reporting of OD was low (